A highly efficient self-power pack system integrating supercapacitors and photovoltaics with an area-saving monolithic architecture. Issue 5 (12th January 2017) - Kim, Junghwan; Lee, Sun Min; Hwang, Yun-Hwa; Lee, Seongyu; Park, Byoungwook; Jang, Jae-Hyung; Lee, Kwanghee
Abstract : Self-charging power packs (SPPs), integrating both a solar cell and energy storage capacitor (EC) into a single device, are very promising energy systems due to their multiple functions of energy harvesting and storage. Abstract : Self-charging power packs (SPPs), integrating both a solar cell and energy storage capacitor (EC) into a single device, are very promising energy systems due to their multiple functions of energy harvesting and storage. Despite their promising potential, however, the monolithic stacking of solid-state ECs onto a large-area solar cell without any external wires is one of the crucial challenges. Here, we successfully demonstrate compact and monolithically stacked SPPs combining a polyvinyl alcohol (PVA)/phosphoric acid (H3 PO4 )-based solid-state supercapacitor and an organometal halide perovskite- or polymer-based solar cell (PeSC or PSC). As a result of robust interconnection formed via a novel electric glue and efficient solar cells with an enlarged photo-harvesting area of up to 100 mm 2, the SPPs exhibited a very high storage efficiency ( η storage ) and overall efficiency ( η overall ) of 80.31% and 10.97%, respectively, for the PeSC-supercapacitor power pack, and 64.59% and 5.07%, respectively, for the PSC-supercapacitor power pack. To the best of our knowledge, the η overall value of our PeSC-supercapacitor power pack is by far the highest reported efficiency for integrated self-charging power packs.